Neural activity in the suprachiasmatic circadian clock of nocturnal mice anticipating a daytime meal. (19th February 2016) - Dattolo, T.; Coomans, C.P.; van Diepen, H.C.; Patton, D.F.; Power, S.; Antle, M.C.; Meijer, J.H.; Mistlberger, R.E.
Highlights: Mice exhibit food anticipatory activity (FAA) to a mid-day meal (usual rest phase). FOS in the SCN circadian clock was reduced during FAA in mice with running disks. Multiple unit activity in the SCN either increased or decreased during FAA. Changes in SCN MUA during behavioral activity were not unique to FAA. The timing of MUA changes during FAA suggests a feedback effect of activity. Abstract: Circadian rhythms in mammals are regulated by a system of circadian oscillators that includes a light-entrainable pacemaker in the suprachiasmatic nucleus (SCN) and food-entrainable oscillators (FEOs) elsewhere in the brain and body. In nocturnal rodents, the SCN promotes sleep in the day and wake at night, while FEOs promote an active state in anticipation of a predictable daily meal. For nocturnal animals to anticipate a daytime meal, wake-promoting signals from FEOs must compete with sleep-promoting signals from the SCN pacemaker. One hypothesis is that FEOs impose a daily rhythm of inhibition on SCN output that is timed to permit the expression of activity prior to a daytime meal. This hypothesis predicts that SCN activity should decrease prior to the onset of anticipatory activity and remain suppressed through the scheduled mealtime. To assess the hypothesis, neural activity in the SCN of mice anticipating a 4–5-h daily meal in the light period was measured using FOS immunohistochemistry and in vivo multiple unit electrophysiology. SCN FOS, quantified by optical density, was significantly reduced at the expected mealtime in food-anticipating mice with access to a running disk, compared to ad libitum -fed and acutely fasted controls. Group differences were not significant when FOS was quantified by other methods, or in mice without running disks. SCN electrical activity was markedly decreased during locomotion in some mice but increased in others. Changes in either direction were concurrent with locomotion, were not specific to food anticipation, and were not sustained during longer pauses. Reduced FOS indicates a net suppression of SCN activity that may depend on the intensity or duration of locomotion. The timing of changes in SCN activity relative to locomotion suggests that any effect of FEOs on SCN output is mediated indirectly, by feedback from neural or systemic correlates of locomotion.